THE OPTIMIZATION OF INVESTIGATIONS BY THE RESMOB SATRESKRIM TEAM TO IMPROVE CRIME CLEARENCE OF VEHICLE THEFT CRIMINAL ACTS IN THE JEPARA POLICE JURISDICTION - Petra Colia (Police Studies Review, 2022)
This research was motivated by an increase in cases of vehicle theft crimes and accompanied by at least the number of disclosures of cases that occurred in jepara police. The resmob team itself is a team that has a task in terms of criminal investigation to find information, find suspects and find evidence. Vehicle theft itself is a conventional crime. Therefore, efforts are needed by the Jepara police department in this case the resmob unit to increase crime clearence of vehicle theft crimes. This research is aimed at describing the investigation conducted by the resmob team in improving crime clearence of vehicle theft crimes. and the analysis knife used on the concept of investigation, the concept of criminal investigation, management theory, competency theory. The results of the study found factors that influence the handling of cases, namely internal and external factors. For internal includes less than optimal management steps including, planning, organizing, implementing, and controlling accompanied by the competence of less than optimal personnel. And the external factor is that the ability of the perpetrator is getting better. Troubleshooting provided by the author in optimizing the investigation of the resmob team to improve crime clearence of vehicle theft crimes. Improve the abilities of the members with education and training. Optimizing all elements of management implementation. And cooperation with external parties to increase crime clearence